(untitled) (American Journal of Interdisciplinary Research and Development, 2026)
This article examines accusatory speech as a distinct component of legal discourse within the framework of pragmatic linguistics. It explores the communicative nature of accusatory speech, its functioning as a speech act, and its interaction with pragmatic categories such as presupposition and implicature. Drawing on established theories in pragmatics and discourse analysis, the study highlights the context-dependent and evaluative nature of accusatory speech and its role in shaping legal discourse. The findings demonstrate that accusatory speech operates as a strategic communicative tool influencing interpretation and decision-making in legal settings.